2015
DOI: 10.1016/j.cimid.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal pathogens, diarrhoea and acute phase proteins in naturally infected dairy calves

Abstract: In this study, the association between Eimeria spp. related signs and innate immune response in dairy calves was examined. Calves (n=100) aged 15-60 days were clinically examined and faecal samples, blood samples and deep nasopharyngeal swabs obtained. The samples were analysed for intestinal pathogens, acute phase proteins and WBC count, and respiratory tract pathogens, respectively. Diarrhoea was diagnosed in 32.6% (23.3-43.0%, 95% CI) of calves. An association between the pathogenic Eimeria spp. and diarrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
11
3
Order By: Relevance
“…In this study, C. parvum was the predominant Cryptosporidium species detected. This is in contrast to reports from calves of comparable age groups from nearby countries Sweden (Silverlås et al, 2010;Björkman et al, 2015) and Finland (Seppä-Lassila et al, 2015), where the dominant species found were C. bovis, and C. bovis and C. ryanae, respectively. The results of this study resemble the results from Belgium, Slovenia and the Czech Republic, where C. parvum accounted for most of the Cryptosporidium findings from calves (Geurden et al, 2007;Soba and Logar, 2008;Kváč et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, C. parvum was the predominant Cryptosporidium species detected. This is in contrast to reports from calves of comparable age groups from nearby countries Sweden (Silverlås et al, 2010;Björkman et al, 2015) and Finland (Seppä-Lassila et al, 2015), where the dominant species found were C. bovis, and C. bovis and C. ryanae, respectively. The results of this study resemble the results from Belgium, Slovenia and the Czech Republic, where C. parvum accounted for most of the Cryptosporidium findings from calves (Geurden et al, 2007;Soba and Logar, 2008;Kváč et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Disease rates of the beef calves in this study reflect those of dairy calves in Nordic countries (Lundborg et al, 2005;Gulliksen et al, 2009;Seppä-Lassila et al, 2015), except that the beef calves had less diarrhoea. The health of beef calves in Central Europe was evaluated by farmers, resulting in higher (Busato et al, 1997) or slightly lower (Slavík et al, 2009) disease prevalence than in this study.…”
Section: Clinical Diseases and Pathogens Of Intestinal And Respiratormentioning
confidence: 52%
“…In Finnish calves, the opposite was observed; Eimeria spp. was associated with diarrhoea, while Cryptosporidium and Giardia were not (Seppä-Lassila et al, 2015). This illustrates that intestinal parasites, including Cryptosporidium, are important agents of disease in calves in the area, but the general clinical picture varies.…”
Section: Parasite Infection Diarrhoea and Halofuginone Lactate Treamentioning
confidence: 90%
“…In neonatal calves, APPs go through significant changes during first 2 to 3 weeks of life (Orro et al, 2008;Tóthová et al, 2015), suggesting that APPs have a role in the adaptation of neonate calves to the new environment. In reindeer calves, lambs, and beef calves, high concentrations of SAA measured in the second week of life have been associated with lower weight gain recorded many months later (Orro et al, 2006;Peetsalu et al, 2013;Seppä-Lassila et al, 2015, 2017.…”
Section: Introductionmentioning
confidence: 99%